Células solares com campo retrodifusor seletivo : passivação frontal e posterior com nitreto de silício - Aquino, Jéssica de (2017)
The majority of silicon solar cells manufactured in an industrial scale is processed in Si-Cz p-type substrates and has the n+pp+ structure. In the last decade, the search for efficiency improvements and fabrication cost reductions has been intensified. Since the cell efficiency is limited by optical losses and surface recombination, the rear and front surface passivation is an alternative for the enhancement of the efficiency. The goal of this dissertation is to develop and analyze solar cells with selective back surface field of boron and aluminum and silicon nitride thin films for the passivation of both surfaces. The silicon nitride thin films were deposited by PECVD (plasma-enhanced chemical vapor deposition), with ratios of silane to ammonia gas flow of 0.875, 1.5 and 2.0, and deposition time of 60 to 100 seconds, adjusted to form the anti-reflection coating. The thickness of the SiNx films, minority carrier lifetime, electrical parameters, minority carrier diffusion length and quantum efficiency were analyzed and compared. The results indicate that the lower the ratio between the silane and ammonia gas flows and the shorter the deposition time, the higher the efficiency of the solar cells manufactured. Due to the passivation, mainly in the front face, caused by the silicon nitride film deposited with the lower ratio of silane and ammonia gas flow and lower deposition time, we observed an increasing oh the internal quantum efficiency, mainly in shorter wavelength. The efficiency reached was 16.0 %, similar to the efficiency of solar cells with aluminium homogeneous back surface field.